Oil sorption capability of treated human hair sorbent for oil sea-water cleanup - Norsuhadat Nordin; Nur Ayuni Aineh; Norfazliana Abdullah (SEGi University, 2024)
This study explored the use of modified human hair as a biosorbent for oil spill clean-up, with a focus on enhancing its oil sorption capacity. Human hair was modified using Sodium Hydroxide (NaOH) and Potassium Hydroxide (KOH) through two methods: hot water treatment at 80°C and mercerization with 5% NaOH and KOH. Structural analysis was conducted, including elemental composition, surface roughness (via Field Emission Scanning Electron Microscopy or FESEM), and hydrophobicity (via wettability tests). The oil sorption capacity was tested using an oil-seawater mixture at different adsorption times (60-100 minutes). Results showed that hair treated with hot water at 100°C achieved the highest oil sorption capacity (2.592 g/g), followed by hair treated with 5% NaOH (2.471 g/g). The optimal adsorption time was found to be 80 minutes, with all samples showing increased oil sorption. The study concluded that hot water treatment significantly improved the surface roughness and hydrophobic properties of the hair, leading to enhanced oil sorption. In comparison, mercerization with NaOH and KOH was less effective in improving the sorption capacity. Raw human hair showed high oil sorption initially, but its effectiveness decreased over extended adsorption times. These findings suggest that modified human hair, especially when treated with hot water, has strong potential for use in oil spill clean-up due to its improved structural and hydrophobic properties.